Characterization of Pressure Distribution in Penetrating Traumatic Brain Injuries - Davidsson, Johan; Risling, Mårten (Frontiers in Neurology, 2015)
Severe impacts to the head commonly lead to localised brain damage. Such impacts may also give rise to temporary pressure changes that produce secondary injuries in brain volumes distal to the impact site. Monitoring pressure changes in a clinical setting is difficult; detailed studies into the effect of pressure changes in the brain call for the development and use of animal models. The aim of this study is to characterise the pressure distribution in an animal model of penetrating traumatic brain injuries (pTBI). This data may be used to validate mathematical models of the animal model and to facilitate correlation studies between pressure changes and pathology. Pressure changes were measured in rat brains while subjected to pTBI for different probe velocities and shapes; pointy, blunt and flat. Experiments on ballistic gel samples were carried out to study the formation of any temporary cavities. In addition, pressure recordings from the gel experiments were compared to values recorded in the animal experiments. The pTBI generated short lasting pressure changes in the brain tissue; the pressure in the contralateral ventricle increased to 8 bar followed by a drop to 0.4 bar when applying flat probes. The pressure changes in the periphery of the probe, in the Cisterna Magna and the spinal canal, were significantly less than those recorded in the contralateral ventricle or the vicinity of the skull base. High speed videos of the gel samples revealed the formation of spherically shaped cavities when flat and spherical probes were applied. Pressure changes in the gel were similar to those recorded in the animals, although amplitudes were lower in the gel samples. We concluded cavity expansion rate rather than cavity size correlated with pressure changes in the gel or brain secondary to probe impact. The new data can serve as validation data for finite element models of the trauma model and the animal and to correlate physical measurements with secondary injuries.